FROM COLLABORATION TO RESILIENCE: MODELING THE MEDIATING ROLE OF SUSTAINABLE TOURISM MANAGEMENT IN COMMUNITY-BASED TOURISM SYSTEMS - Lenny Kurnia Octaviani; Sugiarto; Tonny Hendratono; D. Rudi Susanto (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the influence of multi-stakeholder collaboration on the resilience of tourism activities and to examine the mediating role of sustainable tourism management within a community-based tourism village context. A quantitative explanatory research design was employed, using Partial Least Squares Structural Equation Modeling (PLS-SEM). The research was conducted in Nglanggeran Tourism Village, Special Region of Yogyakarta, Indonesia, with data collection carried out in 2025. A total of 90 respondents were selected through purposive sampling based on their active involvement in village tourism activities. The three main constructs, namely multi-stakeholder collaboration, sustainable tourism management, and tourism activity resilience, were measured using a 5-point Likert scale instrument. PLS-SEM analysis was employed to evaluate the measurement and structural models, encompassing assessments of validity, reliability, R², Q², and hypothesis testing via bootstrapping. Findings indicate that multi-stakeholder collaboration has a positive and significant effect on both sustainable tourism management and tourism activity resilience. Sustainable tourism management also shows a positive and considerable influence on tourism activity resilience. Furthermore, a partial mediation effect was identified, wherein sustainable tourism management strengthens the impact of multi-stakeholder collaboration on the strength of tourism activities. Structured and inclusive multi-stakeholder collaboration, when integrated with sustainable tourism management practices, enhances the resilience of tourism activities in community-based destinations. These results underscore the crucial importance of collaborative governance and sustainable management practices in fostering destination sustainability and resilience.